Rancangan Sistem Informasi Pelayanan Pengaduan Kerusakan Jalan di Dinas Perkimtan Palembang - Al Farissi, M.Fajar; Wijaya, Freddy Kurnia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Information technology has experienced rapid development, strengthened by the presence of the internet, encouraging the creation of e-government to improve public services and government efficiency. One implementation of information technology in this field is a road damage complaint information system. This study aims to design an information system that can be used by the public to report road damage in Palembang City quickly and efficiently, while facilitating the Public Housing and Settlement Area Service (Perkimtan) in following up on the report. This study uses the prototyping method, which allows users to be involved in the system development process through an initial model that is continuously updated. This system is web and mobile-based, which allows online reporting of road damage, complete with photo upload features and damage locations. The results of the study show that this system is able to increase the efficiency of report handling, accelerate the distribution of reports to related officers, and provide better transparency to the public regarding the status of their reports. With this system, the process of handling road damage becomes more coordinated, thereby increasing public satisfaction with public services provided by the Palembang City Perkimtan Service.